Effect of Power Source in ECDM Process with FEM Modeling. (2016) - Paul, Lijo; Korah, Libin V.
Abstract: Electro Chemical Discharge Machining (ECDM) is a hybrid non-conventional manufacturing process which combines the features of Electro Chemical Machining (ECM) and Electro Discharge Machining (EDM). This process is important since it can machine a variety of materials including non-conducting materials like ceramics, composites, alumina, glass, etc. This paper attempts to develop a thermal model of ECDM process for determining the Material Removal Rate (MRR) with direct current (DC) and pulse DC.Comparing both DC and pulse DC on the bases of temperature variations and material removal rate, pulse DC is found to be better than DC with lower temperature range and higher MRR.